Free-trade areas and welfare: An equilibrium analysis - Sang-seung Yi (Fondazione Eni Enrico Mattei (FEEM), 1998)
This paper examines the welfare effects of the formation of a free-trade area (a set of countries that abolish tariffs among member countries but let individual member countries to set external tariffs). If a representative consumer has love-of-variety preferences the welfare function exhibits supermodularity in external tariffs: when a country is constrained to charge lower tariffs on imports of some countries (because of a free-trade agreement) it is in the self-interest of that country to reduce external tariffs as well, because the reduction in external tariffs helps restore a balanced consumption portfolio. The reduction in external tariffs induced by free-trade agreements is shown to be sufficiently large to make non-member countries better off. Since only privately beneficial free-trade agreements are voluntarily signed, the formation a free-trade area is a Pareto improvement. Due to free-riding problems, however, the global free-trade area may not be an equilibrium outcome under either the Open Regionalism rule or the Unanimous Regionalism rule.
Keywords: 330; Freihandelszone; Handelsblock; Wohlfahrtsanalyse; Zollunion; Koalition; Nash-Gleichgewicht; Theorie